Best Practices Regarding the Use of Electronic Environment for Romanian Tourism Development - Irina Maiorescu; Mihai Teodor Negrea; Dorin Vicențiu Popescu; Gabriel Cristian Sabou (Amfiteatru Economic Journal, 2016)
Information and Communication Technology (ICT) plays an important role in all sectors of activity, hence in tourism sector too. Starting from this fact, authors consider as important identifying and implementing best practices in electronic environment for sustainable development of tourism in Romania. Traditional tourism - implying at all stages specialized human support – knows profound modifications. Today, current statistics show that more and more people dive into virtual environment for visualizing new places and finding out new information, for cross border business meetings, for entertainment as well as for communication. Hence, the current paper – presenting the results of a complex quantitative research, aims to discuss about the influence of virtual environment upon tourism in what concerns informing, planning and organizing a trip. The obtained results led towards recommendations for developing ICT facilities, especially for business tourism, for an extensive use of web-GIS applications during the three phases of travel, for improving infrastructure and mobile applications, especially for young people, as well as for implementing digital systems that investigate tourists' behaviour and personalize tourism offers. The final purpose of the paper is to contribute to the development of best practices that lead to economic growth in tourism, by quantifying the impact of electronic environment upon visiting experiences.
Keywords: L83; L86; M39; O33; 330; Information and Communication Technologies (ICT); eTourism; GIS applications; best practices; tourists' behaviour